Pengaruh Kerjasama Tim, Budaya Organisasi dan Pengembangan Karir Terhadap Kepuasan Kerja Pegawai di Bagian Kesekretariatan Dinas Marga dan Bina Konstruksi Provinsi Sulawesi Selatan - Nur Zakiah Khaeriyah Tasrief; Mas'ud, Masdar; Hamid, Sanusi (Innovative: Journal Of Social Science Research, 2025)
The Influence of Teamwork, Organizational Culture, and Career Development on Employee Job Satisfaction in the Secretariat Division of the Public Works and Construction Department of South Sulawesi Province.This study was conducted with the aim of: (1) knowing and analyzing the influence of Teamwork on Employee Job Satisfaction in the Secretariat Division of the Public Works and Construction Department of South Sulawesi Province; (2) knowing and analyzing the influence of Organizational Culture on Employee Job Satisfaction in the Secretariat Division of the Public Works and Construction Department of South Sulawesi Province; (3) knowing and analyzing the influence of Career Development on Employee Job Satisfaction in the Secretariat Division of the Public Works and Construction Department of South Sulawesi Province. This study uses a descriptive research method using a quantitative approach. The sampling technique uses a saturated sampling method or census method, namely all members of the population are used as samples with the number of samples used being 38 civil servants working in the Secretariat Section of the Bina Marga and Bina Konstruksi Service of South Sulawesi Province. In this case, to confirm the hypothesis, the research technique was then analyzed using multiple linear regression analysis techniques supported by the IBM SPSS (Statistical Product and Service Solutions) version 26 application. The results of this study show that:(1) teamwork has a positive and insignificant influence on employee job satisfaction in the Secretariat Division of the South Sulawesi Province Highways and Construction Service; (2) organizational culture has a negative and insignificant influence on employee job satisfaction in the Secretariat Division of the South Sulawesi Province Highways and Construction Service; (3) career development has a positive and significant influence on employee job satisfaction in the Secretariat Division of the South Sulawesi Province Highways and Construction Service. Keywords: Teamwork, Organizational Culture, Career Development, and Job Satisfaction.